ISLAMIC FINANCE IN RUSSIA: PROBLEMS OF FORMATION AND WAY OF THEIR DECISION - IL’JAS ABDULBJAROVICH Zaripov (Мир новой экономики, 2018)
The article is devoted to process of formation of alternative financial model - Islamic finance in our country. Objects of research are: a role, a position of Islamic finance in Russia and the problems interfering their development. The purpose of this research is to prove a demand of the Islamic financial concept within the framework of the Russian economy and vital necessity to eliminate obstacles of development of Islamic finances within national financial sector. The author givesthe external and internal political and economic reasons as arguments, taking into consideration the challenges of current economic situation at global and at national level.Author presents in article the concept, contractual models, its advantages,and optimal ways of evolution of a new financial system in our country. He used following research methods: comparison,systemacity, the analysis, synthesis, and complexity of approach and other methods of scientific analytical research.